Release of nutrients and organic carbon in different soil types from hydrochar obtained using sugarcane bagasse and vinasse - Bento, Lucas Raimundo [UNESP]; Castro, Antônio Joel Ramiro; Moreira, Altair Benedito [UNESP]; Ferreira, Odair Pastor; Bisinoti, Márcia Cristina [UNESP]; Melo, Camila Almeida [UNESP] (Elsevier, 2019)
Hydrothermal carbonization of byproducts from the sugarcane industry generates a solid material (hydrochar) rich in carbon and nutrients with the potential to be used as a soil conditioner. In this context, the objective of this work was to evaluate the nutrient release process from hydrochar with the aim of improving soil quality. To do this, experiments were performed evaluating the concentration of NO3 −, PO4 −3, K, Ca, Mg, Fe and total organic carbon leached from a column filled with soil and different hydrochar proportions during one month. The proportions of hydrochar were 1 and 4% (w/w) applied to sand, ultisol, and oxisol. Nitrogen and phosphorus were immobilized in the soils due to the high organic carbon released that increase microbial activity and to the presence of iron and aluminum oxides, respectively. The oxisol retains part of the carbon released by the hydrochar due to its high content of silt and clay. Only part of the carbon and nutrients of the hydrochar was released, indicating a recalcitrant material. The prepared hydrochar provided nutrients and organic carbon depending on the soil type to which it was applied. This study shows that hydrochar, if applied in the appropriate proportion, can enhance the soil fertility.
Keywords: Fertility; Hydrochar; Oxisol; Soil columns; Terra Preta de Índio soils; Ultisol